Antioxidative and immunogenic properties of catalase-peroxidase protein in Penicillium marneffei. (November 2013) - Pongpom, Monsicha; Sawatdeechaikul, Pritsana; Kummasook, Aksarakorn; Khanthawong, Sophit; Vanittanakom, Nongnuch
Abstract Penicillium marneffei is a significant opportunistic fungal pathogen in Southeast Asia and its ability to survive inside the host macrophages is believed to be important in the establishment of infection. Previously, we isolated a gene encoding a catalase- peroxidase (cpeA) from P. marneffei and showed that the cpeA transcript is specifically upregulated during yeast phase growth at 37°C. In this study, the cpeA transcript was found to be induced during the mycelium to yeast phase transition and during stress conditions induced by hydrogen peroxide treatment. Null mutation of cpeA reduced the fungal tolerance to hydrogen peroxide but not to heat stress. These results indicated that the CpeA plays a crucial role in this fungus' oxidative stress response. Western blot analysis demonstrated that the CpeA induced antibody production in P. marneffei-infected patients, including highly exposed-healthy people. This is the first report that the catalase-peroxidase possesses an immunogenic property in fungi.